The effects of virtual reality and augmented reality technologies on students' story retelling performance. - Bilal Şimşek; Betül Koparan (PLoS ONE)
This study aims to compare the retelling performance of two groups that engaged in reading activities with virtual reality and augmented reality texts. Furthermore, the results of the interventions using these technologies were compared with the results of the printed text reading activity. The study participants comprised 100 students aged 12-13 years studying in a secondary school. The researchers evaluated the students' story-retelling performance through a rubric in the study. In the pre-test stage, the students performed a paper-based reading activity on the texts in the coursebook and their retelling performance was evaluated. In the post-test stage, the reading activities of the two groups were carried out with the intervention of virtual reality and augmented reality. While the pre-test results showed no significant difference between the groups, the post-test results indicated that the augmented reality intervention better supported the students' retelling performance than virtual reality. However, there was no significant difference between the two groups in the sub-categories of setting and characters. Additionally, the virtual reality intervention did not create a significant difference in the sub-categories of characters, event/plot, problem, solution, and total score compared to the printed text reading activity. However, it produced better results in the setting sub-category than the printed text. A positive difference was observed in all sub-categories when the augmented reality intervention was compared to the printed text reading activity. AR showed greater benefits for retelling performance in this study, but further research is needed on long-term retention.